The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fmicb.2015.00463
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and approaches in plasmidome studies—uncovering plasmid diversity disregarding of linear elements?

Abstract: The term plasmid was originally coined for circular, extrachromosomal genetic elements. Today, plasmids are widely recognized not only as important factors facilitating genome restructuring but also as vehicles for the dissemination of beneficial characters within bacterial communities. Plasmid diversity has been uncovered by means of culture-dependent or -independent approaches, such as endogenous or exogenous plasmid isolation as well as PCR-based detection or transposon-aided capture, respectively. High-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 123 publications
0
38
0
3
Order By: Relevance
“…Most of the known plasmids occur in circular form, which is an important feature allowing for their easy isolation using the alkaline lysis method. There are, however, also representatives, mostly from the Borellia, Streptomyces, Nocardia and Rhodococcus genera, which are linear ( 3 ). An important feature of plasmids is that they usually lack genes commonly assigned to primary metabolic processes but rather possess genes improving environmental fitness of the host or coding catabolic or resistance functions ( 4–6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the known plasmids occur in circular form, which is an important feature allowing for their easy isolation using the alkaline lysis method. There are, however, also representatives, mostly from the Borellia, Streptomyces, Nocardia and Rhodococcus genera, which are linear ( 3 ). An important feature of plasmids is that they usually lack genes commonly assigned to primary metabolic processes but rather possess genes improving environmental fitness of the host or coding catabolic or resistance functions ( 4–6 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of plasmids have been identified by chance during the analysis of host bacteria based on specific phenotypes ( 8 ). However, this method of identification is very laborious and cannot provide proper insight into the so-called ‘plasmidome’, which refers to the entire plasmid DNA content of a particular environmental sample independent of cultivation ( 3 ). Although culture-dependent plasmidome studies ( 9–12 ) have significantly contributed to our understanding of mobile genetic elements from a given bacterium or bacterial group, plasmids from the non-cultivable organisms are out of reach using these methods.…”
Section: Introductionmentioning
confidence: 99%
“…They often replicate autonomously in the host using a variety of replication systems. Generally they are circular, however some species carry linear plasmids (Dib et al, 2015;Li et al, 2007). Plasmids carry often genes which provide a benefit to the host, such as additional metabolic capabilities (Rozwandowicz et al, 2018), antimicrobial resistance genes (Carattoli, 2009) and virulence factors that affect host invasion and infection, including type IV secretion systems, toxins, adhesins, invasins and antiphagocytic factors (Johnson & Nolan, 2009;Sengupta & Austin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These non-core genes increase the diversity of a species' pan-genome and can make up around 90% of it 3 , where plasmids contribute a large proportion 4 . Although more and more studies provide insights on the plasmidome [4][5][6][7][8][9][10] , which refers to the entire plasmid DNA of an environmental sample 9 , the mechanisms that keep plasmid diversity are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable progress has been made investigating the persistence conditions of plasmids in a single plasmid -single host [11][12][13][14][15][16][17] or single plasmid -multiple host environment [18][19][20][21][22] , but we are just beginning to understand the role of a co-occurrence of multiple plasmid types, either in a single [23][24][25][26][27][28][29][30][31][32] or multiple host 33 framework. It has been shown that the number, size and functions of the plasmids found in different genera 34 , single species 5,8 or in environmental samples 4,6,7,9,[35][36][37][38][39] can vary remarkably.…”
Section: Introductionmentioning
confidence: 99%